PARTICIPATION OF EMPLOYEES IN MANAGEMENT BODIES OF THE MACEDONIAN SHAREHOLDING COMPANIES - Petkukjeski, PhD Ljupcho; Andonov, PhD Marko; Mihajloski, PhD Zoran; Trajkova, PhD Kate; Ljativ, PhD Samir (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
Joint Stock Company is a company in which shareholders participate with investments in the nominal capital which isdivided into shares and the shareholders are not liable for the obligations of the company.Modern joint-stock companies are companies with enormous economic and other powers. Concentration of capital and labor of these companies gives them a very strong position in the market through which these companies have greatimpact on the economic and political relations as well as on the social situation in the society.Besides the managing bodies (members of the supervisory bodies and non-executive members), the bodies ofmanagement - management (executive directors, board members and other senior workers - managers), shareholdersand employees also are participants in the organization of the company. Each of the participants, including employees hasits place and its role within the activity of the enterprise.Employees are one of the most important factors involved in the realization of the business venture and in the creation ofnew value of the company (profits). As a real consequence of this fact arises the question of their participation in decisionsabout the distribution of newly created value, which can lead to a possible conflict with investors and managers of thecompany.With the participation of employees in the bodies of the shareholders company and in decision-making of importance tothe company, they protect their primarily economic and social rights and interests, and with this, they contributes toeconomic and social peace and stability in the company.The main goal of this paper is to give the legal basis for the practical realization of the right of participation of employees inthe management of the share holders company in the Republic of Macedonia.